The Teaching and Learning Strategy: Do We Need Classroom to Transfer Knowledge and Values to Our Students? - Adha, Muhammad Mona; Wijaya, Apriyanda Kusuma; Ulpa, Eska Prawisudawati; Johnstone, Jack McGregor (International Journal of Social Learning (IJSL), 2024)
Classroom learning is extremely important for students, providing a structured environment supporting their academic, social, and emotional development. Classroom learning allows students to interact with teachers in real time; this offers the opportunity for immediate clarification, feedback, and guidance, which is critical for deeper understanding. Building interactions by seeing stimuli and gestures appropriately takes a classroom where interactions occur naturally which can be observed directly. Online classes present fairly short class meetings and do not involve emotional well between teacher and students. Qualitative research with a case study approach in the article reveals the need for direct interaction in the classroom teaching-learning process. 10 respondents were middle school teachers who taught in several schools in Bandar Lampung. Classrooms must be used as fun spaces filled with motivation for students related to critical social values, cooperation, respect, empathy, critical thinking, and responsibility are essential for the student’s holistic development.